STUDYING THE HISTORY OF SAMARKAND IN THE WORKS OF ALEXANDER MORRISON (Neo Scientific Peer Reviewed Journal, 2024)
Samarkand is one of the most ancient cities not only in Central Asia, but also in the whole world, and is considered one of the most important political and cultural centers with a universal cultural history. The place that Samarkand occupies in the whole world history is incomparable. It would not be an exaggeration to say that this historical and young city has today become a research center in modern historical institutes of various developed countries around the world. This article analyzes Alexander Morrison's information on the history of Samarkand based on sources.